Pengaruh Supportive Educative Berbasis Family Centered Nursing terhadap Kemampuan Keluarga Menstimulasi Perkembangan Motorik Usia 0 – 6 Bulan - Cory Nelia Damayanti; Zakiyah Yasin; Emdat Suprayitno (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
Early age is a golden age, a window of opportunity and a critical period for child development. Providing stimulation as early as possible is very much needed by children as a stimulus for aspects of their development. This is often the case when parents often ignore the result that parents experience ignorance about how to provide stimulation to their children from an early age. This research is a quantitative research with a quasy experimental approach. The population in this study consisted of 90 children aged 0-6 months in Paberasan Village, with a sample size of 46 children. The sampling technique used Simple Random Sampling as many as 23 people each in the control group and the treatment group. This data was collected using the KPSP questionnaire. Data analysis used bivariate analysis with chi-square test. The results of this study indicate that most parents stimulate their children. The results of data analysis on family abilities before stimulation of children based on the family centered nursing model in the post-treatment group obtained a mean result of 36.79 and the post-control group obtained a mean of 30.43 with a pValue of 0.000 (α > 0.05), so there is an influence family ability to stimulate Health workers can carry out screening as early as possible in families in order to increase parents' knowledge in stimulating children's motor development.